Creating a conceptual model for staff professional and personal development - D. N. Karimova (Вестник университета)
To be competitive in the marketplace, a company needs a workforce capable to perform its labour functions effectively, respond flexibly to scientific and technological advances, increasing labour productivity and profits of company. This problem can be solved through staff professional and personal development. The aim of the study is to create a conceptual model of staff professional and personal development. Research methods are theoretical analysis of the problem, study of economic and psychological literature, system analysis, theoretical modelling. The article presents a model for staff professional and personal development based on an integrative approach and a personal developmental principle. It reveals the main factors affecting development, stages and work methods. The introduction of staff development mechanisms based on this model will contribute to improving the organisation’s efficiency.